2013
DOI: 10.1038/nature12116
|View full text |Cite
|
Sign up to set email alerts
|

X-ray phase-contrast in vivo microtomography probes new aspects of Xenopus gastrulation

Abstract: An ambitious goal in biology is to understand the behaviour of cells during development by imaging—in vivo and with subcellular resolution—changes of the embryonic structure. Important morphogenetic movements occur throughout embryogenesis, but in particular during gastrulation when a series of dramatic, coordinated cell movements drives the reorganization of a simple ball or sheet of cells into a complex multi-layered organism1. In Xenopus laevis, the South African clawed frog and also in zebrafish, cell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 33 publications
0
78
0
Order By: Relevance
“…All these only require a clear segmentation of the associated boundaries. Because of this, optimised CGTV should be interesting for 4D livecell imaging, aspiring to the acquisition of long time-lapse series [3,4]. The in vivo data, as reconstructed in the present work, is not contaminated by a high level of statistical photon noise.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…All these only require a clear segmentation of the associated boundaries. Because of this, optimised CGTV should be interesting for 4D livecell imaging, aspiring to the acquisition of long time-lapse series [3,4]. The in vivo data, as reconstructed in the present work, is not contaminated by a high level of statistical photon noise.…”
Section: Discussionmentioning
confidence: 87%
“…Namely, the usefulness of in vivo imaging strongly hinges on a good control of dose effects, thus enabling long time-lapse series of 3D images with weak perturbations induced by the imaging process itself. Recently, embryonic development in the vertebrate model organism Xenopus laevis (African clawed frog) was imaged in vivo via 3D time-lapse series [3,4]. In cases like these a low number of tomographic projections is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing is required to generate the diverging illumination for high magnification and resolution. Note that also for parallel beam propagation imaging it is extremely common to implicitly assume perfect plane wave illumination by performing the conventional flat-field correction [128,[130][131][132][133][134]. In previous studies, we have shown that under these conditions the commonly used standard flat-field correction, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo imaging, e.g., the development in Xenopus laevis (African clawed frog) [1,2], g z is unacceptable at such low values of z in view of the high noise-to-contrast ratio R g z , see Eq. (6) and Fig.…”
Section: Linear Modelsmentioning
confidence: 99%
“…In particular, vertebrate model embryos such as Xenopus laevis (optically opaque) can be imaged in vivo in four dimensions and with micrometer spatial resolution, appealing to X-ray phase contrast [1,2]. As early developmental stages are composed of light elements only, essentially, such embryos act as pure-phase objects from an imaging point of view (δ /β ∼ 10 3 [3] for X-ray energies E ∼ 30 GeV, δ , β representing the projected refractive index n = 1 − δ + iβ (δ = δ (x), β (x) > 0, real).…”
Section: Introductionmentioning
confidence: 99%